Improvement of Salt production quality through threaded filter technology with geomembrane media in Bledug Kuwu, Grobogan, Central Java - Erwin Nofiyanto; Haslina Haslina; Ari Endang Jayati (Community Empowerment, 2025)
Salt is an essential ingredient in everyday life as a cooking spice. Bledug Kuwu salt, produced from the eruption of a mud crater in Kuwu Village, Kradenan District, Grobogan Regency, Central Java Province, resembles coarse salt but has a slightly paler color. The process of making this salt remains simple; it involves flowing the water from the eruption into a reservoir and then evaporating it using bamboo or plastic sheets. The purpose of this community service initiative is to improve the quality of salt production through the application of threaded filter technology (TUF) using geomembrane media in Bledug Kuwu, Grobogan. The methods employed include lectures, discussions, and question-and-answer sessions. The results of the TUF training indicated a positive impact on salt production in Bledug Kuwu. In addition to enhancing participants’ understanding of this technology, farmers also benefited from the provision of HDPE geomembrane plastic. Previously, they used 2-meter white plastic, which was prone to damage and lasted only about a month. However, by switching to HDPE geomembrane plastic, the production of Bledug Kuwu salt increased significantly; salt was formed faster, the price became higher, the installation process was easier, and the lifespan of the materials was extended. Overall, farmers reported significant benefits from the implementation of threaded filter technology (TUF) and the use of HDPE geomembrane plastic.